2019
DOI: 10.48550/arxiv.1909.10245
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Improving CNN-based Planar Object Detection with Geometric Prior Knowledge

Jianxiong Cai,
Jiawei Hou,
Yiren Lu
et al.

Abstract: In this paper, we focus on the question: how might mobile robots take advantage of affordable RGB-D sensors for object detection? Although current CNN-based object detectors have achieved impressive results, there are three main drawbacks for practical usage on mobile robots: 1) It is hard and time-consuming to collect and annotate large-scale training sets.2) It usually needs a long training time. 3) CNN-based object detection shows significant weakness in predicting location. We propose a novel approach for … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…The trained model is also able to detect occluded, overlapped, and partially visible signs. The experimental results showed that the DeepHAZMAT model is more accurate and faster than many other recent and state-or-the-art research works such as [18], [19], and [20]. The developed DNN-based system was fast enough to be implemented in Mobile robots, using a single Intel NUC Corei7 embedded system for robust and real-time hazard label detection, recognition, identification, localisation, and segmentation, thanks to skipping redundant input frames as well as adaptation of the YOLOv3-tiny for our real-time robotics application.…”
Section: Discussionmentioning
confidence: 88%
“…The trained model is also able to detect occluded, overlapped, and partially visible signs. The experimental results showed that the DeepHAZMAT model is more accurate and faster than many other recent and state-or-the-art research works such as [18], [19], and [20]. The developed DNN-based system was fast enough to be implemented in Mobile robots, using a single Intel NUC Corei7 embedded system for robust and real-time hazard label detection, recognition, identification, localisation, and segmentation, thanks to skipping redundant input frames as well as adaptation of the YOLOv3-tiny for our real-time robotics application.…”
Section: Discussionmentioning
confidence: 88%